Repellent Activity of Plant Extracts, Essential Oils and their Combinations against Different Mosquito Species: A Review - Sharma, Disha; Singh, Vandana; Yadav, Manoj Kumar; Patil, Umesh Kumar; Dixit, Vinod Kumar; Yadav, Narayan Prasad (Indian Journal of Natural Products, 2022)
Mosquitoes are majorly responsible for causing vector-borne diseases such as malaria, filariasis, chikungunya, dengue, zika, yellow fever, west nile etc. Aedes, Anopheles, Culex are the main genera among other mosquitoes’ species, that are affecting human beings with such dreadful diseases worldwide. To control the transmission of diseases by mosquitoes generally mosquito nets, ITNs and LLINs, DDT, DEET, IR3535 are being used. Prolong use of these harmful chemicals not only cause development of resistance in mosquitoes but also have shown adverse effects on humans as well as on environment. So, there is a growing urge/need of finding a suitable mosquito repellent from natural origin, that have potential to prevent such vector-borne diseases with least side- effects on humans as well as on environment. In this review, we have enlisted various Essential oils (EO) that are having mosquito repellent properties and some of them such as Cymbopogon nardus, Eucalyptus maculata, Cymbopogon excavatus, Mentha piperita, Azadirachta indica are already used in various mosquito repellent formulations that are being marketed presently. EO of particular plant can be extracted from respective parts of it such as seeds, roots, rhizomes, stems, leaves, bracts, fruits, bark and inflorescences mainly by hydrodistillation and steam distillation. Gas chromatography coupled to mass spectrometry (GC-MS) is the identification technique used for identification of EO constituents. In addition, the combinations of potent EOs are also found to be the best effective way to be used as mosquito repellent so that repellent potential enhanced due to synergism as well as negates the harmful effects of individual oils. The efficiency of essential oils as well as its protection time can also be enhanced by using vanillin and formulation techniques like microencapsulation and nanoemulsion. Based on market coverage as well as economical cost, synthetic repellents are frequently marketed than essential oils but these EOs, extracts or natural products have the potential to provide efficient and safer repellents for humans as well as the environment.
Keywords: Herbal mosquito repellent; Essential oils combinations; Natural products; Anopheles stephensi; Aedes aegypti; Dengue; Malaria